2006
DOI: 10.2527/jas.2005-509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of butyrate, avilamycin, and a plant extract combination on the intestinal equilibrium of early-weaned pigs1

Abstract: We evaluated the effects of 3 additives, sodium butyrate (AC), avilamycin (AB), and a combination of plant extracts (XT), on the productive performance and the intestinal environment of the early-weaned pig. The XT was a standardized mixture with 5% (wt/wt) carvacrol (from Origanum spp.), 3% cinnamaldehyde (from Cinnamonum spp.), and 2% capsicum oleoresin (from Capsicum annum). Pigs (n = 32) weaned at 18 to 22 d of age with an initial BW of 6.0 +/- 0.10 kg were allocated to 8 pens that, in turn, were allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
97
0
22

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 36 publications
14
97
0
22
Order By: Relevance
“…PEs have been reported by several authors to affect the immune system of the intestine. Nofrarías et al (2006) and Manzanilla et al (2006) found reduced counts of intraepithelial lymphocytes in the proximal jejunum after supplementation with carvacrol, cinnamaldehyde and capsicum oleoresin. Sehm et al (2007), after administration of apple pomace or red-wine pomace, observed enlargement of the ileum and the incorporation of Peyer's patches.…”
Section: Discussionmentioning
confidence: 96%
“…PEs have been reported by several authors to affect the immune system of the intestine. Nofrarías et al (2006) and Manzanilla et al (2006) found reduced counts of intraepithelial lymphocytes in the proximal jejunum after supplementation with carvacrol, cinnamaldehyde and capsicum oleoresin. Sehm et al (2007), after administration of apple pomace or red-wine pomace, observed enlargement of the ileum and the incorporation of Peyer's patches.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the studies suggested that supplementation of plant extracts and essential oil blends does not improve performance of weaning pigs, regardless of whether carvacrol or thymol is contained or not (Namkung et al, 2004;Cho et al, 2006;Kommera et al, 2006;Manzanilla et al, 2006;Nofrarias et al, 2006). For example, the dietary supplementation with the plant extract containing 5% (w/w) carvacrol, 3% cinnamaldehyde and 2% capsicum oleoresin at dose of 300 mg/kg does not affect the performance of weaning pigs Nofrarias et al, 2006).…”
Section: Figure 1 Population Of Enterococcus Genus (A) Escherichia Cmentioning
confidence: 99%
“…In piglets fed a butyrate-supplemented diet, the number of colonic goblet cells was significantly increased (94) . In milk-fed calves, butyrate enhanced HSP27 and HSP70 expression in the abomasum and in the colon, but not in the small intestine (8) .…”
Section: Beneficial Effects On Performance and Intestinal Healthmentioning
confidence: 99%
“…In the small intestine, the crypt depth and the villi height increase largely in butyrate-supplemented weaning or weaned pigs (94,117) . Interestingly, when infused in the colon, butyrate was shown to exert trophic effect on ileal and jejunal epithelial cells, presumably indirectly, through a neurohormonal mechanism (114,115) .…”
Section: Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation